2024
DOI: 10.1101/2024.05.20.595020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of JN.1-derived SARS-CoV-2 subvariants SLip, FLiRT, and KP.2 in neutralization escape, infectivity and membrane fusion

Pei Li,
Julia N. Faraone,
Cheng Chih Hsu
et al.

Abstract: SARS-CoV-2 variants derived from the immune evasive JN.1 are on the rise worldwide. Here, we investigated JN.1-derived subvariants SLip, FLiRT, and KP.2 for their ability to be neutralized by antibodies in bivalent-vaccinated human sera, XBB.1.5 monovalent-vaccinated hamster sera, sera from people infected during the BA.2.86/JN.1 wave, and class III monoclonal antibody (Mab) S309. We found that compared to parental JN.1, SLip and KP.2, and especially FLiRT, exhibit increased resistance to COVID-19 bivalent-vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The latter scientific rationale is exemplified by the recent XBB.1.5 monovalent vaccine, where selecting a dominant and antigenically distinct spike protein for the vaccine formulation has led to improved serum neutralization of prevalent variants 1 . However, there have only been very limited studies reported on the antibody responses after JN.1 breakthrough infections 14-16 . Moreover, there is a lack of systematic evaluation of antigenicity of key JN.1 sublineages that carry various combinations of the aforementioned recurrent mutations.…”
Section: Introductionmentioning
confidence: 99%
“…The latter scientific rationale is exemplified by the recent XBB.1.5 monovalent vaccine, where selecting a dominant and antigenically distinct spike protein for the vaccine formulation has led to improved serum neutralization of prevalent variants 1 . However, there have only been very limited studies reported on the antibody responses after JN.1 breakthrough infections 14-16 . Moreover, there is a lack of systematic evaluation of antigenicity of key JN.1 sublineages that carry various combinations of the aforementioned recurrent mutations.…”
Section: Introductionmentioning
confidence: 99%
“…A series of variants with mutations at L455, F456, and R346 convergent hotspot sites emerged including "SLip" variant which has the JN.1 mutations (L455S) with the additional F456L mutation [36]. More recently, we have seen the emergence of the FLiRT variant, which harbors an additional R346T mutation in the backbone of SLip.…”
mentioning
confidence: 99%
“…More recently, we have seen the emergence of the FLiRT variant, which harbors an additional R346T mutation in the backbone of SLip. Recent studies revealed that that F456L (SLip) and R346T (FLiRT) subvariants of JN.1 contribute to further escape of JN.1derived variants from neutralizing antibodies [36,37]. Since January 2024, JN.1 diversified into a number of sublineages, many of which share recurrent mutations R346T ( JN.1.18), F456L ( JN.1.16), T572I ( JN.1.7), or combinations of these mutations (KP.2 variant).…”
mentioning
confidence: 99%